Method for increasing noise immunity of radar "friend or foe" identification systems under the action of intentional correlated interference - Svyd, I.V.; Obod, I.I.; Maltsev, O.S.; Tkach, M.G.; Starokozhev, S.V.; Hlushchenko, A.O.; Chumak , V.S. (Radiotekhnika, 2021)
The paper analyzes the principles of construction and structure of "friend or foe" identification systems. It is revealed, that the party, interested in the existing system, has the ability of unauthorized use of this information resource for long-range determination of air objects coordinates, on the one hand, and distortion of information of this information resource, on the other hand, which leads to unpredictable consequences. It is shown, that the most vulnerable place in the "friend or foe" identification systems is the aircraft transponder, which significantly affects noise stability and noise immunity of the identification systems of air objects. The paper proposes a method of hereditary transition to noise-immune "friend or foe" identification systems based on synchronous networks of identification systems, which allows expanding significantly the methods of servicing requests and methods of constructing systems. This method of constructing identification systems eliminates the existing problem of dispersed identification systems, as well as the problem of temporal matching of signals coming from primary and secondary radar systems. The proposed method of hereditary transition to noise-immune "friend or foe" identification systems makes it possible to exclude the possibility of unauthorized access to identification information resources by an interested party, significantly increases the noise immunity of the identification system as a whole.